High-performance silver-copper-based wear-resistant composite material and preparation method thereof
Through plasma ball milling and vacuum hot pressing sintering, high-performance silver-copper-based wear-resistant composite materials are prepared, which solves the problems of low density and high cost of the existing processes, and achieves the effects of high wear resistance and tensile strength.
Patent Information
- Application Number
- CN202411401438.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
AI Technical Summary
The existing preparation process of silver-copper-based wear-resistant composite materials has problems such as low density, poor microstructure controllability, complex process flow and high cost, and cannot meet the needs of high performance.
By plasma ball milling of silver-copper alloy powder and microalloyed element powder, silver-copper alloy powder was obtained, and plasma ball milling was then plasma ball milled with the reinforced phase to form a composite powder. Then vacuum hot press sintering and homogenizing heat treatment were carried out, and finally hot extrusion was performed to prepare a high-performance silver-copper-based wear-resistant composite material.
It achieves the improvement of wear resistance and tensile strength of the alloy material without affecting the conductivity, and can be used for the preparation of conductive slip rings to meet the needs of high performance and low cost.
Smart Images

Figure CN119464804A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silver-copper based composite materials, and in particular relates to a high-performance silver-copper based wear-resistant composite material and a preparation method thereof. Background Art
[0002] The brush-slip ring system is a key component of aerospace rotary power transmission. In this system, the conductive slip ring slides in the conductive ring with the help of elastic brushes, thereby achieving power and signal transmission between two relatively rotating parts. As the core component of the brush-slip ring system, the service performance of the conductive slip ring, such as mechanical properties, high wear resistance, low friction coefficient and self-lubrication, directly determines the service life and reliability level of the brush-slip ring system. However, the service environment of the conductive slip ring is extremely complex. Under the coupling of multiple fields such as electric field, magnetic field, temperature field and stress field, as well as the coupling of multiple factors such as current, dynamic load and electrochemical corrosion, adhesive wear and abrasive wear will occur. At the same time, brittle fracture, micro-motion wear and arc erosion may also occur, which will have a serious impact on the electrical transmission performance and working reliability of the conductive slip ring. With the continuous extension of the design life of detectors in the aerospace field, the substantial increase in the power and power density of electrical instruments, and the significant increase in the application of high-voltage busbars, higher requirements are put forward for the comprehensive performance and service reliability of the conductive slip ring.
[0003] At present, the materials for preparing the conductive slip rings required under harsh service conditions can be mainly divided into gold alloys, silver alloys and wear-resistant composite materials prepared with them as the matrix. The conductive slip rings prepared by gold alloys and silver alloys have excellent friction reduction and wear resistance, low contact resistance and good storage stability, but their high preparation cost is not conducive to their promotion to civilian products. Therefore, it is necessary to develop a new type of silver alloy-based wear-resistant composite material as a new conductive slip ring material to meet the requirements of low cost, high reliability and long service life of the brush-slip ring system.
[0004] For example, CN111069497 A discloses a method for preparing a high-hardness silver-copper-nickel alloy conductive ring, wherein the preparation method is to melt the silver-copper-nickel alloy into an ingot, homogenize the heat treatment, forge, and roll the silver-copper-nickel alloy slab; then, the silver-copper-nickel alloy slab is subjected to heat treatment and wire cutting to finally obtain the silver-copper-nickel alloy conductive ring. CN201711027249.1 discloses a high-performance, long-life space equipment precision conductive slip ring and a preparation method thereof, wherein the preparation method is to use plasma spraying to form a core-shell structure of Cu-TiO 2The composite powder is directly sprayed on the metal slip ring substrate, and the good wear resistance of the composite coating is used to protect the metal substrate of the conductive slip ring, thereby greatly extending the service life of the conductive slip ring and improving the reliability of long-term stable operation. CN202111398234.2 discloses a composite material of a conductive slip ring and a method for preparing a test piece thereof. The preparation method is to mix molybdenum disulfide, carbon tubes and copper powder into a composite powder, and then sinter it to obtain a copper-based composite material.
[0005] At present, the preparation process of silver-copper based wear-resistant composite materials is mainly divided into smelting and powder metallurgy processes, which have problems such as low density, poor microstructure controllability, complex process flow and high cost, and therefore cannot meet the demand for high-performance silver-copper based wear-resistant composite materials. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a high-performance silver-copper based wear-resistant composite material and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a high-performance silver-copper based wear-resistant composite material comprises the following steps:
[0009] (1) subjecting silver-copper alloy powder and microalloying element powder to plasma ball milling to obtain silver-copper alloy powder;
[0010] (2) plasma ball milling the silver-copper alloy powder and the reinforcement phase to obtain a composite powder;
[0011] (3) performing vacuum hot pressing sintering on the composite powder to obtain a bulk silver-copper based composite material;
[0012] (4) homogenizing and hot extruding the bulk silver-copper based composite material to obtain a high-performance wear-resistant silver-copper based composite material;
[0013] The silver-copper alloy powder is AgCu10, AgCu20 or AgCu30; the micro-alloying element powder is at least two of chromium powder, cobalt powder, tin powder, nickel powder and titanium powder; the mass percentage of the micro-alloying element powder in the total mass of the silver-copper alloy powder and the micro-alloying element powder is 0.1-0.2wt.%.
[0014] Compared with using one plasma ball milling, the present invention uses two plasma ball millings to achieve microalloying and the synergistic effect of microalloying and reinforcement, and improves the wear resistance and tensile strength of the alloy material without affecting the conductivity.
[0015] As a preferred embodiment of the present invention, in the step (1), the rotation speed of the plasma ball milling treatment is 900-1200 r / min, the ball milling time is 1-6 h, the discharge power is 300-600 W, the ball-to-material ratio is 50:1, and the atmosphere is high-purity argon.
[0016] The parameters of the plasma ball milling of the present invention can achieve microalloying of the added elements within the above range.
[0017] As a preferred embodiment of the present invention, the reinforcing phase is at least one of graphene, carbon nanotubes, molybdenum disulfide, and MXene, and the volume proportion of the reinforcing phase in the composite powder is 1-5 vol.%.
[0018] More preferably, when the reinforcing phase is graphene, the prepared high-performance silver-copper based wear-resistant composite material has the best tensile strength and wear resistance.
[0019] As a preferred embodiment of the present invention, in step (2), the rotation speed of the plasma ball milling treatment is 900-1200 r / min, the ball milling time is 1-3 h, the discharge power is 300-600 W, the ball-to-material ratio is 20:1, and the atmosphere is high-purity argon.
[0020] The present invention can avoid the disadvantage of destroying the reinforcing phase caused by plasma ball milling to achieve microalloying of elements through the second plasma ball milling treatment within the above-mentioned limited range. Therefore, the plasma ball milling defined in the present invention can achieve microalloying of elements without destroying the structure of the reinforcing phase and reducing the conductivity, wear resistance and tensile strength of the alloy material.
[0021] As a preferred embodiment of the present invention, the vacuum hot pressing sintering is specifically carried out under vacuum conditions at 600-800°C for 60-180 minutes, the sintering pressure is 50MPa, and the vacuum degree is less than 10 -3 Pa, the heating rate is 10°C / min, which can avoid cracking of the alloy during hot extrusion. If the parameters of vacuum hot pressing sintering are not within the range of the present invention, the risk of cracking of the alloy during hot extrusion is increased.
[0022] As a preferred embodiment of the present invention, the temperature of the homogenization treatment is 500-600°C and the time is 120 minutes. The present invention prevents the alloy material from cracking during the extrusion process by performing a homogenization treatment after vacuum hot pressing sintering and before hot extrusion. If the homogenization treatment step is missing, the material prepared after vacuum hot pressing sintering is directly hot extruded, and cracks during the hot extrusion process and cannot be used.
[0023] As a preferred embodiment of the present invention, the temperature of the hot extrusion is 400-500°C, and the extrusion ratio is 5-15.
[0024] The present invention also claims protection for the high-performance silver-copper-based wear-resistant composite material prepared by the preparation method of the high-performance silver-copper-based wear-resistant composite material.
[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention performs plasma ball milling on silver-copper alloy powder microalloyed with at least two elements of chromium powder, cobalt powder, tin powder, nickel powder and titanium powder, and then continues plasma ball milling after adding a reinforcing phase, so as to prepare a high-performance silver-copper based wear-resistant composite material which has good density, wear resistance and tensile strength without affecting the conductivity, and can be used for the preparation of conductive slip rings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart for the preparation of high-performance silver-copper based wear-resistant composite materials. DETAILED DESCRIPTION
[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0028] Example 1
[0029] like Figure 1 As shown, a method for preparing a high-performance silver-copper based wear-resistant composite material comprises the following steps:
[0030] (1) Plasma ball milling is performed on AgCu10 alloy powder with a purity of 99.9% and a particle size of about 29 μm, and Ni powder and Ti powder with a purity of 99.9% and a particle size of about 1 μm, so that Ni and Ti elements are dispersed on the surface of the AgCu10 alloy powder; wherein the rotation speed is 900 r / min, the ball milling time is 2 h, the discharge power is 300 W, the ball-to-material ratio is 50:1, and the ball mill is filled with high-purity argon gas for protection; the weight percentage of Ni element in the alloyed powder is 1.0%, the weight percentage of Ti element is 1.0%, and the remainder is AgCu10.
[0031] (2) subjecting the AgCu10-Ni1-Ti1 metal powder and graphene obtained in step (1) to homogenization plasma ball milling; wherein the rotation speed is 900 r / min, the ball milling time is 2 h, the discharge power is 400 W, the ball-to-material ratio is 20:1, and the ball mill is filled with high-purity argon gas for protection; the volume percentage of graphene in the composite powder is 2.0%, and the remainder is AgCu10-Ni1-Ti1.
[0032] (3) subjecting the composite powder treated in step (2) to vacuum hot pressing sintering, homogenization heat treatment and hot extrusion to obtain a silver-copper based composite material; wherein the sintering temperature is 600° C., the holding time is 120 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -3Pa, heating rate 10℃ / min; the temperature of homogenization heat treatment is 500℃, the time is 120min; the extrusion temperature is 400℃, the extrusion ratio is 5, and finally a high-performance silver-copper based wear-resistant composite material is obtained.
[0033] The high-performance silver-copper-based wear-resistant composite material prepared in Example 1 has a tensile strength of 287 MPa and a friction coefficient of 0.35.
[0034] Example 2
[0035] like Figure 1 As shown, a method for preparing a high-performance silver-copper based wear-resistant composite material comprises the following steps:
[0036] (1) Plasma ball milling is performed on AgCu20 alloy powder with a purity of 99.9% and a particle size of about 20 μm, and Cr powder and Ti powder with a purity of 99.9% and a particle size of about 1 μm, so that Cr and Ti elements are dispersed on the surface of the AgCu20 alloy powder; wherein the rotation speed is 1000 r / min, the ball milling time is 3 h, the discharge power is 400 W, the ball-to-material ratio is 50:1, and the ball mill is filled with high-purity argon gas for protection; the weight percentage of Cr element in the alloyed powder is 0.5%, the weight percentage of Ti element is 0.5%, and the remainder is AgCu20.
[0037] (2) subjecting the AgCu20-Ti0.5-Cr0.5 metal powder and graphene obtained in step (1) to homogenization plasma ball milling; wherein the rotation speed is 1000 r / min, the ball milling time is 2 h, the discharge power is 300 W, the ball-to-material ratio is 20:1, and the ball mill is filled with high-purity argon gas for protection; the volume percentage of graphene in the composite powder is 2.0%, and the remainder is AgCu20-Ti0.5-Cr0.5.
[0038] (3) subjecting the composite powder treated in step (2) to vacuum hot pressing sintering, homogenization heat treatment and hot extrusion to obtain a silver-copper based composite material; wherein the sintering temperature is 700° C., the holding time is 120 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -3 Pa, heating rate 10℃ / min; the temperature of homogenization heat treatment is 600℃, the time is 120min; the extrusion temperature is 500℃, the extrusion ratio is 10, and finally a high-performance silver-copper based wear-resistant composite material is obtained.
[0039] The high-performance silver-copper-based wear-resistant composite material prepared in Example 2 has a tensile strength of 288 MPa and a friction coefficient of 0.38.
[0040] Example 3
[0041] like Figure 1As shown, a method for preparing a high-performance silver-copper based wear-resistant composite material comprises the following steps:
[0042] (1) Plasma ball milling is performed on AgCu20 alloy powder with a purity of 99.9% and a particle size of about 20 μm, and Ni powder and Co powder with a purity of 99.9% and a particle size of about 1 μm, so that Ni and Co elements are dispersed on the surface of the AgCu20 alloy powder; wherein the rotation speed is 1100 r / min, the ball milling time is 3 h, the discharge power is 500 W, the ball-to-material ratio is 50:1, and the ball mill is filled with high-purity argon gas for protection; the weight percentage of Ni element in the alloyed powder is 2%, the weight percentage of Co element is 2%, and the remainder is AgCu20.
[0043] (2) The AgCu20-Ni2-Co2 metal powder and MXene obtained in step (1) are subjected to homogenization plasma ball milling treatment; wherein the rotation speed is 1100 r / min, the ball milling time is 3 h, the discharge power is 400 W, the ball-to-material ratio is 20:1, and the ball mill is filled with high-purity argon for protection; the volume percentage of MXene in the composite powder is 2.0%, and the rest is AgCu20-Ni2-Co2.
[0044] (3) subjecting the composite powder treated in step (2) to vacuum hot pressing sintering, homogenization heat treatment and hot extrusion to obtain a silver-copper based composite material; wherein the sintering temperature is 700° C., the holding time is 180 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -3 Pa, heating rate 10℃ / min; the temperature of homogenization heat treatment is 600℃, the time is 120min; the extrusion temperature is 450℃, the extrusion ratio is 15, and finally a high-performance silver-copper based wear-resistant composite material is obtained.
[0045] The high-performance silver-copper-based wear-resistant composite material prepared in Example 3 has a tensile strength of 321 MPa and a friction coefficient of 0.45.
[0046] Example 4
[0047] like Figure 1 As shown, a method for preparing a high-performance silver-copper based wear-resistant composite material comprises the following steps:
[0048] (1) Plasma ball milling is performed on AgCu30 alloy powder with a purity of 99.9% and a particle size of about 10 μm, and Cr powder and Co powder with a purity of 99.9% and a particle size of about 1 μm, so that Cr and Co elements are dispersed on the surface of the AgCu30 alloy powder; wherein the rotation speed is 1100 r / min, the ball milling time is 2 h, the discharge power is 400 W, the ball-to-material ratio is 50:1, and the ball mill is filled with high-purity argon gas for protection; the weight percentage of Cr element in the alloyed powder is 1%, the weight percentage of Co element is 1%, and the remainder is AgCu30.
[0049] (2) subjecting the AgCu30-Cr1-Co1 metal powder and carbon nanotubes obtained in step (1) to homogenization plasma ball milling; wherein the rotation speed is 1100 r / min, the ball milling time is 2 h, the discharge power is 400 W, the ball-to-material ratio is 20:1, and the ball mill is filled with high-purity argon gas for protection; the volume percentage of carbon nanotubes in the composite powder is 2.0%, and the remainder is AgCu30-Cr1-Co1.
[0050] (3) subjecting the composite powder treated in step (2) to vacuum hot pressing sintering, homogenization heat treatment and hot extrusion to obtain a silver-copper based composite material; wherein the sintering temperature is 750° C., the holding time is 120 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -3 Pa, heating rate 10℃ / min; the temperature of homogenization heat treatment is 500℃, the time is 120min; the extrusion temperature is 450℃, the extrusion ratio is 10, and finally a high-performance silver-copper based wear-resistant composite material is obtained.
[0051] The high-performance silver-copper-based wear-resistant composite material prepared in Example 4 has a tensile strength of 275 MPa and a friction coefficient of 0.42.
[0052] Comparative Example 1
[0053] The only difference between the preparation method of a high-performance silver-copper based wear-resistant composite material in this comparative example and that in Example 1 is that the plasma ball milling treatment in steps (1) and (2) is replaced by a common ball milling process. In step (1), the ball milling speed is 1100 r / min, the ball milling time is 2 h, and the ball-to-material ratio is 50:1; in step (2), the ball milling speed is 1100 r / min, the ball milling time is 2 h, and the ball-to-material ratio is 20:1.
[0054] The high-performance silver-copper-based wear-resistant composite material prepared in Comparative Example 1 has a tensile strength of 228 MPa and a friction coefficient of 0.47.
[0055] Comparative Example 2
[0056] A method for preparing a high-performance silver-copper based wear-resistant composite material comprises the following steps:
[0057] (1) AgCu10 alloy powder with a purity of 99.9% and a particle size of about 29 μm, Ni powder and Ti powder with a purity of 99.9% and a particle size of about 1 μm, and graphene are subjected to plasma ball milling to obtain a composite powder; wherein the rotation speed is 900 r / min, the ball milling time is 2 h, the discharge power is 300 W, the ball-to-material ratio is 50:1, and the ball mill is filled with high-purity argon gas for protection; the weight percentage of Ni element in the AgCu10 alloy powder, Ni powder and Ti powder is 1.0%, the weight percentage of Ti element is 1.0%, and the remainder is AgCu10; the volume percentage of graphene in the composite powder is 2.0%, and the remainder is AgCu10-Ni1-Ti1.
[0058] (2) subjecting the composite powder treated in step (1) to vacuum hot pressing sintering, homogenization heat treatment and hot extrusion to obtain a silver-copper based composite material; wherein the sintering temperature is 600° C., the holding time is 120 min, the sintering pressure is 50 MPa, and the vacuum degree is less than 10 -3 Pa, heating rate 10℃ / min; the temperature of homogenization heat treatment is 500℃, the time is 120min; the extrusion temperature is 400℃, the extrusion ratio is 5, and finally a high-performance silver-copper based wear-resistant composite material is obtained.
[0059] The high-performance silver-copper-based wear-resistant composite material prepared in Comparative Example 2 has a tensile strength of 224 MPa and a friction coefficient of 0.51.
[0060] Comparative Example 3
[0061] The only difference between the preparation method of a high-performance silver-copper based wear-resistant composite material in this comparative example and that in Example 1 is that: in the step (1), AgCu10 alloy powder with a purity of 99.9% and a particle size of about 29 μm and Ni powder with a purity of 99.9% and a particle size of about 1 μm are subjected to plasma ball milling treatment, so that the Ni element is dispersed on the surface of the AgCu10 alloy powder; wherein the rotation speed is 900 r / min, the ball milling time is 2 h, the discharge power is 300 W, the ball-to-material ratio is 50:1, and the ball mill is filled with high-purity argon for protection; the weight percentage of the Ni element in the alloyed powder is 2.0%, and the remainder is AgCu10.
[0062] The high-performance silver-copper-based wear-resistant composite material prepared in Comparative Example 3 has a tensile strength of 236 MPa and a friction coefficient of 0.48.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-performance silver-copper based wear-resistant composite material, characterized in that: The steps include: (1) subjecting silver-copper alloy powder and microalloying element powder to plasma ball milling to obtain silver-copper alloy powder; (2) plasma ball milling the silver-copper alloy powder and the reinforcement phase to obtain a composite powder; (3) performing vacuum hot pressing sintering on the composite powder to obtain a bulk silver-copper based composite material; (4) homogenizing and hot extruding the bulk silver-copper based composite material to obtain a high-performance wear-resistant silver-copper based composite material; The silver-copper alloy powder is AgCu10, AgCu20 or AgCu30; the micro-alloying element powder is at least two of chromium powder, cobalt powder, tin powder, nickel powder and titanium powder; the mass percentage of the micro-alloying element powder in the total mass of the silver-copper alloy powder and the micro-alloying element powder is 0.1-0.2wt.%.
2. The method for preparing the high-performance silver-copper based wear-resistant composite material according to claim 1, characterized in that: In the step (1), the rotation speed of the plasma ball milling treatment is 900-1200 r / min, the ball milling time is 1-6 h, the discharge power is 300-600 W, the ball-to-material ratio is 50:1, and the atmosphere is high-purity argon.
3. The method for preparing the high-performance silver-copper based wear-resistant composite material according to claim 1, characterized in that: The reinforcing phase is at least one of graphene, carbon nanotubes, molybdenum disulfide, and MXene, and the volume proportion of the reinforcing phase in the composite powder is 1-5 vol.%.
4. The method for preparing the high-performance silver-copper based wear-resistant composite material according to claim 1, characterized in that: In the step (2), the rotation speed of the plasma ball milling treatment is 900-1200 r / min, the ball milling time is 1-3 h, the discharge power is 300-600 W, the ball-to-material ratio is 20:1, and the atmosphere is high-purity argon.
5. The method for preparing the high-performance silver-copper based wear-resistant composite material according to claim 1, characterized in that: The vacuum hot pressing sintering is specifically carried out under vacuum conditions at 600-800°C for 60-180 minutes, with a sintering pressure of 50MPa and a vacuum degree of <10 -3 Pa, the heating rate is 10℃ / min.
6. The method for preparing the high-performance silver-copper based wear-resistant composite material according to claim 1, characterized in that: The temperature of the homogenization treatment is 500-600° C. and the time is 120 minutes.
7. The method for preparing the high-performance silver-copper based wear-resistant composite material according to claim 1, characterized in that: The temperature of the hot extrusion is 400-500° C., and the extrusion ratio is 5-15.
8. A high-performance silver-copper-based wear-resistant composite material prepared by the method for preparing a high-performance silver-copper-based wear-resistant composite material according to any one of claims 1 to 7.
Citation Information
Patent Citations
A high-performance, long-life precision conductive slip ring for space equipment and its preparation method
CN107794486B
Composite material of conductive slip ring and preparation method of test piece of composite material
CN114086025A
Cited By
Self-lubricating silver-based composite material for space conductive slip ring and preparation method of self-lubricating silver-based composite material
CN121228040A